2002
DOI: 10.1088/0031-9155/47/4/306
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis and determination of thepwallcorrection factor for60Co γ-ray beams for Wellhöfer Roos-type plane-parallel chambers

Abstract: The wall perturbation correction factor p(wall) in 60Co for Wellhöfer Roos-type plane-parallel ionization chambers is determined experimentally and compared with the results of a previous study using PTW-Roos chambers (Palm et al 2000 Phys. Med. Biol. 45 971-81). Five ionization chambers of the type Wellhöfer PPC-35 (or its equivalent PPC-40) are used for the analysis. Wall perturbation correction factors are obtained by assuming N(D,air) chamber factors determined by cross-calibration in a high-energy electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 5 publications
1
11
1
Order By: Relevance
“…The cobalt-60 calibration coefficients for plane-parallel chambers obtained in August 2011, eight months following initial calibrations, are systematically lower by 0.6% on average (with 0.3% standard deviation) between calibrations while those for the Farmer chambers show no change within 0.1%. This is consistent with the stability results observed by Palm et al 5 However, calibration coefficients for individual chambers were different by up to 1.2% after the eight month period between measurements. At the time of this recalibration, some chambers were behaving strangely in terms of leakage, as discussed in Sec.…”
Section: Iiig Long-term Stabilitysupporting
confidence: 93%
See 2 more Smart Citations
“…The cobalt-60 calibration coefficients for plane-parallel chambers obtained in August 2011, eight months following initial calibrations, are systematically lower by 0.6% on average (with 0.3% standard deviation) between calibrations while those for the Farmer chambers show no change within 0.1%. This is consistent with the stability results observed by Palm et al 5 However, calibration coefficients for individual chambers were different by up to 1.2% after the eight month period between measurements. At the time of this recalibration, some chambers were behaving strangely in terms of leakage, as discussed in Sec.…”
Section: Iiig Long-term Stabilitysupporting
confidence: 93%
“…Christ et al 6 indicated no problems with long-term stability but without quantification. Palm et al 5 indicate that the standard deviation of calibration coefficients for Roos chambers over a period of several months was 0.6%-0.7%. Bass et al 33 report that for 20 NACP and Roos chambers the average repeatability of calibration coefficients is within 0.1%-0.2% but with some chambers giving repeat results that differ by up to 1%.…”
Section: Iiig Long-term Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Christ et al93 suggested that long-term stability was not an issue for plane-parallel chambers. The standard deviation of calibration coefficients measured by Palm et al94 in cobalt-60 three or four FACTORS ferences of up to 1 % were observed between repeated calibrations. These levels of stability are consistent with the observations of this work.The unexpected sensitivity of leakage currents to levels of relative humidity discussed above suggests that plane-parallel chambers are more sensitive to environmental conditions than cylindrical chambers.…”
mentioning
confidence: 84%
“…A cross-calibration procedure against a stable cylindrical chamber would avoid these problems, although this would need to be done each time these chambers are used.3.3 Measured k Q factorsUncertainty budget: The uncertainty budget for measured k Q factors and calibration coefficients for plane-parallel chambers in photon beams is provided in table 3.1, derived using the ISO "Guide to the expression of uncertainty in measurement" 82 recommendations. The use of the indirect method of calibration against a stable secondary standard cylindrical chamber is discussed in chapter 2 and the individual components of uncertainty are discussed in the preceding sections 3.1 and 3.2.Chamber-to-chamber variability of measured k Q factors: Variability of measured k Q factors for plane-parallel chambers of the same type has been investigated by several authors,36,55,86,93,94,96 usually based on measurements in cobalt-60. The main reason that these chambers were not recommended for use in photon beams by reference dosimetry protocols 10,11 was evidence for unacceptable (up to 3.6 %) chamberto-chamber variations of cobalt-60 P wall values for chambers of the same type 36.…”
mentioning
confidence: 99%